Penggunaan Geogebra dalam Geometri Ruang - Zulhendri Zulhendri; Joni Joni (Jurnal Pengabdian Masyarakat (abdira), 2022)
The rapid development of technology opens up new opportunities and ways in doing many things, including to develop the world of education. One of the learning media that is currently developing so rapidly is a computer with various relevant programs. One of the computer programs that can be used as a medium for learning mathematics is the Geogebra program. The purpose of this community service is to find out the use of Geogabra in geometric geometry at Sei Putih High School, Kampar Riau Regency. The methods that will be used in this activity are direct observation, interviews, presentations, and questions and answers. The results of this service activity received a positive response from the partner schools and the teachers participating in the workshop. This can be seen from the enthusiasm of the training participants and the seriousness of the participants during the activity. The participants hoped for further training so that the competence of the Sei Putih High School mathematics teacher in learning using Geogebra would increase.